Mirror‐mode storms inside stream interaction regions and in the ambient solar wind: A kinetic study. Issue 1 (27th January 2013) - Enríquez‐Rivera, O.; Blanco‐Cano, X.; Russell, C. T.; Jian, L. K.; Luhmann, J. G.; Simunac, K. D. C; Galvin, A. B.
Abstract : [1] Mirror‐mode structures have been found in the solar wind at various heliocentric distances with different missions. Recently, STEREO has observed mirror‐mode waves present as trains of holes and also as humps in the magnetic field magnitude. In some cases, mirror‐mode trains last for very long periods of time and have been called "mirror‐mode storms". We present case studies of mirror‐mode storms observed in the solar wind using STEREO data in three different locations: in the downstream region of the forward shock of a stream interaction region, inside a stream interaction region far from the forward shock, and also in the ambient solar wind. To make a formal identification of the mirror mode, we determine wave characteristics using minimum variance analysis. Finally, we perform a kinetic dispersion analysis and discuss the possible origin of mirror‐mode structures evaluating curves of growth for different regimes of proton temperature anisotropies in a plasma with a He component. Key Points: Mirror mode storms (MMSs) are common features observed inside SIRs We suggest that MMSs are generated locally via the mirror mode instability Alpha particle enhancements play an important role in the generation of MMSs